Re-discovery and re-description of the true Plagiopholis styani (Boulenger, 1899) (Serpentes, Pseudoxenodontidae), with the taxonomic status of the populations previously considered as P. styani - Shuo Liu; Zengyang Luo; Xi Xiao; Caichun Peng; Dongru Zhang; Shize Li (Biodiversity Data Journal, 2025)
The type locality of Plagiopholis styani is in Wuyishan Mountain, Fujian Province, China and, currently, this species is considered to be widely distributed in southern China and northern Vietnam. However, since this species was described, there have been very few reports of this species from its type locality.We re-discovered Plagiopholis styani from its type locality and collected one topotypic specimen. By comparing the sequence of the topotypic specimen of P. styani with the sequences on GenBank, we found that the so-called sequences of P. styani on GenBank do not belong to P. styani. Based on the topotypic specimen of P. styani, we re-describe this species and provide molecular data of the true P. styani for the first time. Combining the sequences on GenBank and literature, we consider that the population from Sichuan and Guizhou Provinces, previously regarded as P. styani, to represent a new species of Plagiopholis. The taxonomic status of the populations previously considered as P. styani from other provinces of China and northern Vietnam still needs further evaluation.